Identification of Ggc Repeat Expansions in zfhx3 Among Chilean Movement Disorder Patients - Chana-Cuevas, P (John Wiley and Sons Inc, 2025)
Background: Hereditary ataxias are genetically diverse, yet up to 75% remain undiagnosed due to technological and financial barriers. The GGC repeat expansion in ZFHX3, responsible for spinocerebellar ataxia type 4 (SCA4), has only been described in individuals of Northern Europeandescent. Objective: Uncover the genetic etiology of suspected hereditary movement disorders. Methods: We performed Oxford Nanopore long-read genome sequencing on 15 individuals with suspected hereditary movement disorders. Using variant calling and ancestry inference tools. Results: We identified ZFHX3 GGC expansions (47–55 repeats) in 4 patients with progressive ataxia, polyneuropathy, and vermis atrophy. One presented with rapidly progressive parkinsonism–ataxia, expanding the known phenotype. Longer expansions correlated with earlier onset and severity. All carriers shared single nucleotide variants (SNVs) associated with the Swedish founder haplotype, and methylation analysis confirmed allele-specific hypermethylation. Conclusion: These represent the first SCA4 cases identified outside Northern Europe. Our findings highlight the value of long-read sequencing in resolving undiagnosed movement disorders. Published 2025. This article is a U.S. Government work and is in the public domain in the USA. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. Published 2025. This article is a U.S. Government work and is in the public domain in the USA. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: Latin American Population; Long Read Sequencing; Spinocerebellar Ataxias; Tandem Repeat Expansions; ZFHX3 gene